The Impact of Brexit on the UK's Trade - Hryshkova, Lina (2021)
The aim of my bachelor thesis is to review the impact of Brexit on the UK´s trade. The theoretical part of the thesis presents aspects related to the historical past of Great Britain and their connection to Brexit, its explanation and understanding, an overview of the most important factors of the 2016 Referendum, and trade relations between Great Britain and the European Union. The practical part is mainly about the review of current analytical surveys devoted to the issue of Brexit and their general evaluation in regards to the trade of the United Kingdom and its trading partners.